👤

1-4*x-5-5*x+2=6*x-6-8*x-3 Na szybko

Odpowiedź :

Odpowiedź:

1-4*x -5-5*x+2= 6*x-6-8*x-3

 1-4x -5 -5x +2= 6x-6-8x-3

  -4x -5x -6x +8x= -3 -6 -2 -1 +5

 -7x= -7  /*(-1)

       7x=7 /:7

          x=1

spr...   1-4*1 -5 -5*1+2= 6*1 -6-8*1-3

              1-4 -5-5+2= 6-6-8-3

                    -11= -11

                        L=P

Szczegółowe wyjaśnienie:

Odpowiedź:

1-4*x-5-5*x+2=6*x-6-8*x-3

1-4x-5-5x+2=6x-6-8x-3

-4x-5x-6x+8x=-6-3-1-2+5

-7x=-7   /:(-7)

x=1

Szczegółowe wyjaśnienie: